Pengaruh Celebrity Endorser dan Kualitas Produk terhadap Keputusan Pembelian Produk MS GLOW di Badung, Bali - Ni Made Ella Dwi Purwati; Saortua Marbun (Journal Research of Management, 2024)
Understanding and analyzing how celebrity endorsement (X1) and product quality (X2) affect consumer decisions to purchase MS GLOW is what this study aims to do. This research examines the relationship between product quality and celebrity endorsement in influencing consumer purchase of MS GLOW (Y). By using concentrated sample size interviews as a data collection technique, the respondents were those who had seen MS GLOW Nagita Slavina cosmetic advertisements and had bought and used the product twice. 18 responses, multiplied by 5 , equals 90. Research employs multiple linear regression analysis and data collection through observation, interviews, documentation and questionnaires. Descriptive analysis, tests for consistency and reliability, traditional assumption tests, specific linear regression tests, f tests, and tests are a few of the approaches used to examine the data. The findings indicated that product quality (X2) and celebrity (X1) had significant and real differences. Positive consumer opinion about purchasing MS GLOW products. The product quality variable variance (X2) in this statement is 0.274. Give to the MS GLOW business to increase celebrity endorsements and improve product quality so that consumers can buy their products in Badung, Bali.